CIRNA project inception meetings held in Uganda and Kenya - Wanyama, Ibrahim; Leitner, Sonja; Slater, Annabel (International Livestock Research Institute, 2024)
This blog post summarizes the inception meetings held for the CIRNA project at national and district level in Kenya and Uganda.